Die Reintegrationsphase der iranischen Agrarreform - Planck, Ulrich (ERDKUNDE, 1975)
Four approaches are being used in Iran to re-integrate, in both micro- and macro-economic terms, the many small individual farms which were fragmented by land reform and which temporarily more or less dropped out of the national economy. (1) the traditional approach, for which there are a whole series of social advantages, links a number of share croppers and share tenants directly to the join farming companies common in Iranian sharecropping. (2) the co-operative approach has its roots in the legislation under which every beneficiary of land reform had to become a member of a rural co-operative. Formal ism, bureaucracy and centralism have, until recently, hindered the ability of the co-operative movement in Iran to make a decisive contribution to the solution of the re integration problem. (3) the revolutionary approach consists of collectivising the farms in the capitalist organisational forms of a land holders society (Wahid-i Sahami-i Zira-i) and an agricultural joint stock company (Shirkat-i Sahami-i Zira-i). In this approach, the goal of re-integration and rapid modernisation of agricultural production can be achieved but only at the expense of major social sacrifices e. g. loss of the independence gained from land reform, and only with the help of large state subsidies. (4) the growth-oriented approach involves encouragement of large-scale agriculture and the formation of agro-business units. Against the economic and technical advantages of this solution must be set the social drawbacks of communal infrastructure burdens, local employment monopolies and social tension.